Investigating Long-Term Behaviour of X-ray Binaries Using Archival Data - M. M. Kotze; P. A. Charles (Acta Polytechnica CTU Proceedings, 2015)
Long term modulations have been detected in a wide variety of both low and high-mass X-ray binaries. The All Sky Monitor on board the Rossi X-ray Timing Explorer provides the most extensive (~15 years) and sensitive X-ray archive for studying such behaviour. Since those variations were often intermittent and/or aperiodic, we used a time-dependent Dynamic Power Spectrum method to examine how the modulations themselves vary with time in a systematic way. Some were found to be remarkably stable, while others show a range of properties, from even longer variability time-scales to quite chaotic behaviour.